2010
DOI: 10.1103/physrevb.81.195401
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Pd atomic chain in a hydrogen atmosphere

Abstract: The formation of a Pd atomic chain in a hydrogen atmosphere was investigated by measurements of conductance and vibrational spectroscopy of a single molecular junction and the theoretical calculation. While atomic chains were not formed for clean 3d and 4d metals, in the case of Pd ͑a 4d metal͒ atomic chains could be formed in the presence of hydrogen. Stable atomic chains with two different atomic configurations were formed when the Pd atomic contact was stretched in a H 2 atmosphere: highly conductive short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 20 publications
(57 reference statements)
10
35
0
Order By: Relevance
“…Hydrogen molecule appears dissociated and two H atoms move to the side of the electrode pyramids. Similar side attachment of hydrogen has been reported by Kiguchi et al [25] for hydrogenated monomer Pd SACs. We, therefore, employed a monomer Ti SAC, placed two H atoms on the contact side, and carried out the energy optimization [26].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Hydrogen molecule appears dissociated and two H atoms move to the side of the electrode pyramids. Similar side attachment of hydrogen has been reported by Kiguchi et al [25] for hydrogenated monomer Pd SACs. We, therefore, employed a monomer Ti SAC, placed two H atoms on the contact side, and carried out the energy optimization [26].…”
Section: Resultssupporting
confidence: 66%
“…It, however, remains a possibility that contaminant atoms might come from within the electrodes, not from environment. Among possible gas species that would give rise to the 0.9G 0 peak, the likeliest candidate should be hydrogen because hydrogen is known for reducing the SAC conductance of various d -band transition metals from ∼ 2G 0 to a value around ∼ 1G 0 [11,[20][21][22][23][24][25]. Smit et al [20] showed for hydrogenated Pt SACs that a hydrogen molecule is sandwiched by Pt electrodes to form a straight Pt-H-H-Pt contact.…”
Section: Resultsmentioning
confidence: 99%
“…The other strong signals found at ±17 meV for H 2 in the IETS spectrum are due to conformational switching of the molecule in the tunnel junction. [11][12][13][14][15][16][17][18][19][20][21] As previously mentioned, the energy of the switching is extremely sensitive to coverage, tip state, and tipsurface separation. [17][18][19][20][21] There are also inelastic peaks around ±4 meV for H 2 .…”
mentioning
confidence: 91%
“…[22,23] This was the first demonstration of H 2 rotational spectra on a bare metal surface by IETS, which raises the question of what makes Au(110) a more suitable substrate than Cu(111), [ 17,18] Ag(111), [19] or nanojunctions made of various metals. [9][10][11][12][13][14][15][16] It is also unclear if rotational IETS probes single molecules or molecular ensembles.…”
mentioning
confidence: 99%
“…The conductance of Au and Cu atomic contacts decreases from 1 G 0 (2e 2 /h) to 0.5 G 0 by introducing CO to the contact at 4 K, which was explained by the scattering of the conduction electrons by the CO molecules adsorbed on the metal atomic contacts [9]. The adsorption of hydrogen molecules on Co or Pd atomic contacts decreases the conductance of the metal atomic contacts, together with the stabilization of the metal atomic contact [10,11]. The stabilization of the Co and Pd contacts leads to the formation of the single atomic chains.…”
Section: Introductionmentioning
confidence: 99%